Mechanism-based thresholds of toxicological concern (TTC) for developmental and reproductive toxicity of anticancer compounds - Stanard, Brad, author; Hanneman, William, advisor; Legare, Marie, committee member; Bouma, Gerrit, committee member; Schaeffer, Joshua, committee member (Colorado State University. Libraries, 2015)
To view the abstract, please see the full text of the document.